Results of research of the combined seeder for strip sowing of grasses into sod - V. A. Sysuev; S. L. Demshin; S. V. Gaididei (Аграрная наука Евро-Северо-Востока)
The development of ecological agriculture has aroused interest to the technology of increasing the productivity of natural forage lands, which consists in strip sowing of grasses with mechanical tillage in the sod of strips, the size of which ensures the successful development of seedlings without the use of chemicals. Several models of seeders SDK have been developed and mass-produced to implement this technology. A further development of this type of machines is the creation of a mounted seeder SDK-2.8M, intended for direct strip sowing of grass seeds into sod with the application of a starting dose of mineral fertilizers. To evaluate the efficiency of the seeder SDK-2.8M in the autumn of 2022, stand and field tests were carried out in the fields of the North-East Federal Research Center. Stand tests on sowing seeds of meadow fescue and red clover showed that the range of gear ratios of the seeder from 0.104 to 0.900 allows to set the seeding rate in the interval of 2.5-140.4 kg/ha. The sowing part ensures uniform distribution of seeds over the feed rolls and the stability of sowing by each feed roll in accordance with agrotechnical requirements. The deviation of the actual seeding rate from preassigned (6.0 kg/ha) for sowing fescue is 2.6%, clover – 2.3%; uneven seeding between feed rolls for fescue – 3.61%, for clover – 5.36%; seeding instability for fescue – 4.83%, for clover – 6.03%. Field tests revealed that the seeder stably performs tillage and clover sowing, maintains the working width and the installation depth of tillage. The average tillage depth was equal to 68 mm, the crumbling of the soil (fraction up to 25 mm) – 85.1%, the average depth of seeding – 16.4 mm, density after rolling – 1.1 g/cm3 .The use of a frame of the original design made it possible to reduce the number of assembly units of the tillage part and auxiliary mechanisms, which reduced the mass of the seeder by 640 kg, in comparison with SDKP-2.8M, while maintaining agrotechnical performance indicators.